Sei sulla pagina 1di 23

Bessel Functions

Project for the Penn State - Gttingen Summer School on Number Theory
Martin Kreh
Content i
Content
1 The Bessel dierential equation 1
1.1 Bessel functions of rst and second kind . . . . . . . . . . . . . . . . . . . 1
1.2 Modied Bessel functions of rst and second kind . . . . . . . . . . . . . . 3
2 Properties of the Bessel functions 5
2.1 Generating function . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 5
2.2 Special values . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 10
2.3 Integral representations . . . . . . . . . . . . . . . . . . . . . . . . . . . . 11
2.4 Dening Bessel functions through the generating function . . . . . . . . . 15
2.5 Asymptotics . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 16
2.6 Graphs of Bessel functions . . . . . . . . . . . . . . . . . . . . . . . . . . . 18
2.7 Integral Transforms . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 19
References 21
Martin Kreh The Bessel Functions
1 The Bessel dierential equation 1
1 The Bessel dierential equation
In the rst chapter, we introduce the (modied) Bessel dierential equation and deduce
from it the (modied) Bessel functions of rst and second kind. This will be done via a
power series approach. We decided to start from a dierential equation, since this seems
kind of naturally. We will point out later that we could have dened the Bessel function
in an other, equivalent, way.
1.1 Bessel functions of rst and second kind
In this section we study the the so called Bessel equation
x
2
y

+ xy

+ (x
2
n
2
)y = 0
for n N, which can for example be obtained by the separation of the wave equation in
cylindric or polar coordinates. Since this is a second order dierential equation, we will
have two linearly independent solutions. We will now start to construct a rst solution.
We take as approach for a solution y a power series. It will be convenient to write
y(x) = x
n

k=0
b
k
x
k
.
Then we have
xy

(x) = nx
n

k=0
b
k
x
k
+ x
n

k=0
kb
k
x
k
and
x
2
y

(x) = n(n 1)x


n

k=0
b
k
x
k
+ 2nx
n

k=0
kb
k
x
k
+ x
n

k=0
k(k 1)x
k
.
We further have
x
2
y(x) = x
n

k=2
b
k2
x
k
when setting b
2
:= b
1
:= 0. Plugging in the dierential equation yields
0 = n(n 1)x
n

k=0
b
k
x
k
+ 2nx
n
+ nx
n

k=0
b
k
x
k
+ x
n

k=0
kb
k
x
k
+ x
n

k=2
b
k2
x
k
n
2
x
n

k=0
b
k
x
k
Martin Kreh The Bessel Functions
1 The Bessel dierential equation 2
= x
n

k=0
(n(n 1)b
k
+ 2nkb
k
+ k(k 1)b
k
+ nb
k
+ kb
k
+ b
k2
n
2
b
k
)x
k
= x
n

k=0
(2nkb
k
+ k
2
b
k
+ b
k2
)x
k
.
Comparing coecients gives
k(k + 2n)b
k
+ b
k2
= 0.
Since b
1
= 0 we get b
1
=
b
1
1+2n
= 0 and recursively b
2k1
= 0 for all k as long as
2n is not a negative whole number. But in this case the recursion will also be fulllled if
b
2k1
= 0 for all k. So it remains to consider even k. Here we have no condition on b
0
.
We can choose it freely and will do so later. Now if n / N we get
b
2k
=
b
2k2
4k(n + k)
and this yields inductively
b
2k
= (1)
k
b
0
4
k
k!(n + k)(n + k 1) (n + 1)
.
It is convenient to choose b
0
=
1
2
n
n!
. So together we get
y(x) =
_
x
2
_
n

k=0
(1)
k
k!(n + k)!
_
x
2
_
2k
.
This is convergent due to the quotient criterion, therefore we have indeed constructed a
solution for the Bessel equation.
We also want to construct a solution for complex order . Here we need to exchane
the factorial with the Gamma function. Then we get
J

(x) =
_
x
2
_

k=0
(1)
k
(k + 1)( + k + 1)
_
x
2
_
2k
This is valid unless n N. But in this case we can just write
J
n
(x) :=
_
x
2
_
n

k=n
(1)
k
(k + 1)(n + k + 1)
_
x
2
_
2k
=
_
x
2
_
n

k=0
(1)
n+k
(n + k + 1)(k + 1)
_
x
2
_
2n+2k
Martin Kreh The Bessel Functions
1 The Bessel dierential equation 3
= (1)
n
J
n
(x)
and of course this solves the Bessel equation.
Now we want to determine a linearly independent solution. First, we describe how J

behaves if x 0. From the power series expansion, we immediately get


lim
x0
J

(x) =
_

_
0, () > 0
1, = 0
, () < 0, / Z
.
This means that J

and J

are two linearly independent solutions if / Z. If Z,


they are linearly dependent. Since (1)
n
= cos n, the function J

(z) cos J

(z) is
a solution of the Bessel equation, which vanishes if n N
0
. Therefore, we dene
Y

(x) =
cos()J

(x) J

(x)
sin()
.
for / Z. Then for n Z the limit
Y
n
(x) := lim
n
Y

(x)
exists, as can be shown by LHospitals rule, and J

and Y

are two linearly independent


solutions of the Bessel equation for all C. This can e.g. be shown be computing the
Wronskian determinant.
1.2 Modied Bessel functions of rst and second kind
The modied Bessel equation is given by
x
2
y

+ xy

(x
2
+
2
)y = 0.
Analog to the previous section we can compute a solution of this dierential equation
using the power series approach. This gives
I

(x) =
_
x
2
_

k=0
1
(k + 1)( + 1 + k)
_
x
2
_
2k
Martin Kreh The Bessel Functions
1 The Bessel dierential equation 4
As before, we search for a second, linearly independent solution. This will, for / Z, be
given by
K

(x) =

2
I

(x) I

(x)
sin()
and its limit for n Z exists.
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 5
2 Properties of the Bessel functions
In this chapter we will prove some properties of Bessel functions. There are of course
more interesting facts, in particular, there are connections between Bessel functions and,
e.g. Legendre polynomials, hypergeometric functions, the usual trigonometric functions
and much more. These can be found in [Wat22] and [GR00]
2.1 Generating function
Many facts about Bessel functions can be proved by using its generating function. Here
we want to determine the generating function.
Theorem 2.1 We have
e
x
2
(zz
1
)
=

n=
J
n
(x)z
n
(2.1)
i.e. e
x
2
(zz
1
)
is the generating function of J
n
(x).
Proof: We have
e
x
2
z
e

x
2
1
z
=

m=0
(
x
2
)
m
m!
z
m

k=0
(1)
k
(
x
2
)
k
k!
z
k
=

n=
_
_
_

mk=n
m,k0
(1)
k
(
x
2
)
m+k
m!k!
_
_
_
z
n
=

n=
_

k=0
(1)
k
(n + k)!k!
_
x
2
_
2k
_
x
2
_
n
_
z
n
=

n=
J
n
(x)z
n
.
q.e.d.
We can use this generating function to prove some standard results.
Lemma 2.2 We have
cos x = J
0
(x) + 2

n=1
(1)
n
J
2n
(x),
sin(x) = 2

n=0
(1)
n
J
2n+1
(x),
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 6
1 = J
0
(x) + 2

n=1
J
2n
(x).
Proof: Directly from (2.1) with z = e
i
, i sin =
1
2
(z
1
z
) we get
cos(xsin )+i sin(xsin ) = e
ixsin
=

n=
J
n
(x)e
in
=

n=
J
n
(x)(cos(n)+i sin(n))
so
cos(xsin ) = J
0
(x) + 2

n=1
J
2n
(x) cos(2n)
and
sin(xsin ) = 2

n=0
J
2n+1
(x) sin((2n + 1)).
This gives the results with =

2
and = 0, respectively. q.e.d.
Lemma 2.3 We have
J
n
(x) = J
n
(x) = (1)
n
J
n
(x)
for all n Z.
Proof: To show the rst equality, we make the change of variables x x, z z
1
in
the generating function. Then the function does not change and we get

n=
J
n
(x)z
n
=

n=
J
n
(x)z
n
=

n=
J
n
(x)z
n
and comparing coecients gives the result. The second equality follows analog with the
change of variable z z
1
. q.e.d.
Lemma 2.4 We have for any n Z
2J

n
(x) = J
n1
(x) J
n+1
(x),
2n
x
J
n
(x) = J
n+1
(x) + J
n1
(x),
d
dx
(x
n
J
n
(x)) = x
n
J
n1
(x). (2.2)
Proof: The rst statement follows, when we dierentiate equation (2.1) with respect to
x:
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 7

n=
J
n
(x)z
n
=
1
2
_
z
1
z
_
e
x
2
(z
1
z
)
=
1
2
z

n=
J
n
(x)z
n

1
2z

n=
J
n
(x)z
n
=

n=
1
2
(J
n1
(x) J
n+1
(x))z
n
.
Comparing coevients yields the result.
The second statement follows completely analog when considering the derivative with
respect to z.
Adding the two equations and multiplying with x
n
/2 gives the third result. q.e.d.
With the last two lemmata we can describe some integrals with Bessel functions via a
dierent Bessel function.
Lemma 2.5 For any n Z we have
_
x
n+1
J
n
(x) dx = x
n+1
J
n+1
(x) and
_
x
n+1
J
n
(x) dx = x
n+1
J
n+1
(x).
Proof: The rst equation follows directly from (2.2). For the second one, we use (2.2)
and lemma 2.3 to get
_
x
n+1
J
n
(x) dx =
_
x
n+1
(1)
n
J
n
(x) dx = (1)
n
x
n+1
J
n+1
(x) = x
n+1
J
n+1
.
q.e.d.
We have already seen, that J
2
0
(x) + 2

n=1
J
2
n
(x) = 1. With a bit more work, we can
also deduce a result for

J
n+m
(x)J
n
(x) with m = 0.
Lemma 2.6 We have for any m = 0
J
2
0
(x) + 2

n=1
J
2
n
(x) = 1 and

n=
J
n+m
(x)J
n
(x) = 0.
Proof: We multiply equation (2.1) with the equation where z z
1
to get
1 =

k=
J
k
(x)z
k

n=
J
n
(x)z
n
=

m=
_

n=
J
n+m
(x)J
n
(x)
_
z
m
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 8
=

n=
J
2
n
(x) +

mZ
m=0
_

n=
J
n+m
(x)J
n
(x)
_
z
n
.
Comparing coecients gives
1 =

n=
J
2
n
(x) = J
2
0
(x) + 2

n=1
J
2
n
(x)
and
0 =

n=
J
n+m
(x)J
n
(x)
for all m = 0. q.e.d.
Lemma 2.7 We have

nZ
J
n
(x) = 1.
Proof: This follow by setting z = 1 in (2.1). q.e.d.
Lemma 2.8 We have
J
n
(x + y) =

kZ
J
k
(x)J
nk
(y)
for all n Z.
Proof: This follow through

nZ
J
n
(x + y) = exp
_
1
2
(x + y)(t t
1
)
_
= exp
_
1
2
x(t t
1
)
_
exp
_
1
2
y(t t
1
)
_
=

kZ
J
k
(x)t
k

mZ
J
m
(y)t
m
=

nZ
_

kZ
J
k
(x)J
nk
(y)
_
t
n
and comparing coecients. q.e.d.
Most of the results hold (in a similar form) also for the other three Bessel functions.
Since the proofs are anlog, we will only state the results.
Theorem 2.9 (Results for J
n
(x), Y
n
(x) and K
n
(x))
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 9
The generating function for the I
n
(x) is e
x
2
(z+z
1
)
, i.e.
e
x
2
(z+z
1
)
=

n=
I
n
(x)z
n
.
We have for all n Z
Y
n
(x) = Y
n
(x) = (1)
n
Y
n
(x),
I
n
(x) = (1)
n
I
n
(x) = I
n
(x),
K
n
(x) = (1)
n
K
n
(x) = K
n
(x).
For all n Z we have
Y
n1
(x) + Y
n+1
(x) =
2n
x
Y
n
(x), Y
n1
(x) Y
n+1
(x) = 2Y

n
(x),
I
n1
(x) I
n+1
(x) =
2n
x
I
n
(x), I
n1
(x) + I
n+1
(x) = 2I

n
(x),
K
n+1
(x) K
n1
(x) =
2n
x
K
n
(x), K
n1
(x) + K
n+1
(x) = 2K

n
(x).
Indeed this and the next two sets of formulae, as well as those for J
n
(x), hold also
for complex orders, as can be shown through the series representation.
We have for all n Z
d
dx
(x
n
Y
n
(x)) = x
n
Y
n1
(x),
d
dx
(x
n
I
n
(x)) = x
n
I
n1
(x),
d
dx
(x
n
K
n
(x)) = x
n
K
n1
(x).
For all n Z there holds
_
x
n+1
Y
n
(x) dx = x
n+1
Y
n+1
(x),
_
x
n+1
Y
n
(x) = x
n+1
Y
n+1
(x),
_
x
n+1
I
n
(x) dx = x
n+1
I
n+1
(x),
_
x
n+1
I
n
(x) = x
n+1
I
n+1
(x),
_
x
n+1
K
n
(x) dx = x
n+1
K
n+1
(x),
_
x
n+1
K
n
(x) = x
n+1
K
n+1
(x).
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 10
We have for all m Z, m = 0
I
2
0
(x) + 2

n=1
(1)
n
I
2
n
(x) = 1 and

n=
(1)
n
I
n+m
(x)I
n
(x) = 0.
We have

n=
I
k
(x) = e
x
.
It holds
I
n
(x + y) =

kZ
I
k
(x)I
nk
(x).
2.2 Special values
In this section we want to examine how the Bessel functions look like when we plug in
some special values.
Lemma 2.10 If
1
2
+Z, the Bessel functions are elementary functions.
1. We have
J1
2
(x) = Y

1
2
(x) =
_
2
x
sin(x),
J

1
2
(x) = Y1
2
(x) =
_
2
x
cos(x),
I1
2
(x) =

2xsinh(x),
I

1
2
(x) =
_
2
x
cosh(x),
K1
2
(x) = K

1
2
(x) =
_

2x
e
x
.
2. There are polynomials P
n
(x), Q
n
(x) with
deg P
n
= deg Q
n
= n, P
n
(x) = (1)
n
P
n
(x), Q
n
(x) = (1)
n
Q
n
(x)
such that for any k N
0
J
k+
1
2
(x) =
_
2
x
_
P
k
_
1
x
_
sin(x) Q
k1
_
1
x
_
cos(x)
_
,
J
k
1
2
(x) = (1)
k
_
2
x
_
P
k
_
1
x
_
cos(x) + Q
k1
_
1
x
_
sin(x)
_
,
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 11
Y
k+
1
2
(x) = (1)
k1
J
k
1
2
(x)
Y
k
1
2
= (1)
k
J
k+
1
2
(x),
I
k+
1
2
(x) =
_
2
x
_
i
k
P
k
_
i
x
_
sinh(x) + i
k1
Q
k1
_
i
x
_
cosh(x)
_
,
I
k
1
2
(x) =
_
2
x
_
P
k
_
1
x
_
cosh(x) Q
k1
_
1
x
_
sinh(x)
_
,
K
k+
1
2
(x) = K
k
1
2
(x) =
_

2x
_
i
k
P
k
_
1
ix
_
sin(x) + i
k1
Q
k1
_
1
ix
_
e
x
_
.
Proof: The rst formulae follow directly from the series representations of J

and I

,
the denitions of Y

and K

and the properties of the -function. For example, we have


J1
2
(x) =
_
x
2

k=0
(1)
k
(k + 1)(k +
3
2
)
_
x
2
_
2k
=
_
x
2

k=0
(1)
k
k!
(2k+1)!

k!2
2k+1
_
x
2
_
2k
=
_
2
x

k=0
(1)
k
(2k + 1)!
x
2k+1
=
_
2
x
sin x
and
Y

1
2
(x) =
cos(

2
)J

1
2
(x) J1
2
(x)
sin(

2
)
= J1
2
(x).
The rest follows from the recurrence formulas of the last section. q.e.d.
Directly from the denitions, we also get
I
n
(x) = i
n
J
n
(ix) and K
n
(x) =

2
i
n1
(J
n
(ix) + iY
n
(ix)).
2.3 Integral representations
In this section we will give an integral representation for each of the four Bessel functions
that we have introduced. There are much more representations as can be shown here, see
e.g. [Wat22] and [GR00].
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 12
Theorem 2.11 For all n, x C we have
J

(x) =
1

_
0
cos(xsin t t) dt
sin()

_
0
e
xsinh(t)t
dt,
Y

(x) =
1

_
0
sin(xsin t t) dt
1

_
0
e
xsinh(t)
(e
t
+ cos()e
t
) dt,
I

(x) =
1

_
0
e
xcos t
cos(t) dt
sin()

_
0
e
xcosh(t)t
dt,
K

(x) =

_
0
e
xcosh(t)
cosh(t) dt.
Proof: We use the representation
1
(z)
=
1
2i
_

t
z
e
t
dt where

is some contour from


, turning around 0 in positive direction and going back to . Then we get
J

(x) =
(x/2)

2i
_

k=0
(1)
k
(x/2)
2k
t
k1
k!
e
t
dt =
(x/2)

2i
_

t
1
e
tx
2
/(4t)
dt.
Let t =
x
2
u. Then we get
J

(x) =
1
2i
_

u
1
e
(x/2)(u
1
u
)
du
for some contour of the same kind. Now let u = e
w
. Then the contour , given as
rectangular with vertices i, i, i, + i without the right edge is the image of
a suitable (see gure 2.1). So we get
Figure 2.1: The contours for the integral.
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 13
J

(x) =
1
2i
_

e
w
e
xsinh(w)
dw =
1
2i
(I
1
+ I
2
I
3
)
with
I
1
=

e
it
e
xsinh(it)
i dt,
I
2
=

_
0
e
(i+t)
e
xsinh(i+t)
dt,
I
3
=

_
0
e
(i+t)
e
xsinh(i+t)
dt.
We have
1
2i
I
1
=
1
2i

e
it
e
xsinh(it)
i dt
=
1
2
_
_

_
0
e
i(xsin tt)
dt +
0
_

e
i(xsin tt)
dt
_
_
=
1
2

_
0
e
i(xsin tt)
+ e
i(xsin tt)
dt
=
1

_
0
cos(xsin t t) dt
which gives the rst part. Further,
1
2i
(I
2
I
3
) =
1
2i

_
0
e
(i+t)
e
xsinh(i+t)
dt

_
0
e
(i+t)
e
xsinh(i+t)
dt
=
1
2i

_
0
e
xsinh tt
(e
i
e
i
) dt
=
sin()

_
0
e
xsinh tt
dt
which gives the second part. This proves the rst result.
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 14
For Y

, we note that
sin()Y

(x) = cos()J

(x) J

(x) =
I
1


sin()

I
2
with
I
1
= cos()

_
0
cos(xsin(t) (t)) dt

_
0
cos(xsin(t) + t) dt,
I
2
=

_
0
e
xsinh(t)
(cos()e
t
+ e
t
) dt.
Since
cos() cos(xsin(t) t) = cos(xsin(t) + ( t)) + sin() sin(xsin(t) t)
and

_
0
cos(xsin(t) + ( t)) dt =

_
0
cos(xsin(t) + t) dt,
we have I
1
= sin()
_

0
sin(xsin(t) t) dt and this proves the formula for / Z.
Because of the continuity, we therefore get it for all .
The formula for I

is proven completely analog to that for J

and that for K

follows
then from the denition, similarly to those for Y

. q.e.d.
With this theorem we can again follow that Y
n
and K
n
exist for n Z.
With the generating function, these formulae can be proven even simplier, at least for
n Z. We will show this as an example for the functions J
n
.
We use

e
int
dt = 2
0
n
to get

e
iz sin
e
in
d =

kZ
J
k
(x)

e
ik
e
in
d = 2J
n
(x).
So
J
n
(x) =
1
2

e
i(xsin n)
=
1

_
0
cos(xsin n) d.
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 15
2.4 Dening Bessel functions through the generating function
As we mentioned before, we wanted to start with the dening dierential equation. We
could have also dened the Bessel function J
n
(x) (at least for integer n) through its
generating function. On this way, we also could have developed the series and integral
representation:
Theorem 2.12 Let the functions y
n
(x) be dened by
e
x
2
(zz
1
)
=

n=
y
n
(x)z
n
Then we have
y
n
(x) =
_
x
2
_
n

k=0
(1)
k
(n + k)!k!
_
x
2
_
2k
and y
n
(x) =
1

_
0
cos(xsin n) d.
Proof: First, the Cauchy integral formula gives us
y
n
(x) =
1
2i
_

e
x
2
(tt
1
)
t
n+1
dt
for any simply closed contour around 0.
First we use the substitution t =
2u
x
and the series representation of e
x
to get
y
n
(x) =
1
2i
_

e
4u
2
x
2
4u
(
2
x
)
n+1
u
n+1
2
x
du
=
1
2i
_
x
2
_
n
_

e
u
e

x
2
4u
u
n1
du
=
_
x
2
_
n

m=0

k=0
(1)
k
m!k!
_
x
2
_
2k
1
2i
_

u
mkn1
du
=
_
x
2
_
n

l=0
(1)
k
(n + k)!k!
_
x
2
_
2k
.
Choosing the contour t = e
i
we get
y
n
=
1
2
2
_
0
e
x
2
(e
i
e
i
)
e
ni
d
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 16
=
1
2
2
_
0
exp(xi sin ni) d
=
1

_
0
cos(xsin n) d.
q.e.d.
From this integral representation we can then easily, using partial integration, see that
this function solves the Bessel dierential equation.
2.5 Asymptotics
Now we want to use the proven integral representations to get asymptotic formulae.
Theorem 2.13 For x R, x we have
J

(x)
_
2
x
cos(x

4


2
),
Y

(x)
_
2
x
sin(x

4


2
),
I

(x)
_
1
2x
e
x
,
K

(x)
_

2x
e
x
.
Proof: J

and Y

:
The second integrals in both of the representations go to 0 exponentially, therefore
we have
J

(x) + iY

(x) =
1

_
0
e
i(xsin tt)
dt +O(x
A
)
for all A. Substitution gives
J

(x) + iY

(x) =
2e
i/2

(I
1
(x) + I
2
(x)) +O(x
A
)
with
I
1
(x) =
/3
_
0
e
ixcos t
cosh(t) dt, I
2
(x) =
/2
_
/3
e
ixcos t
cosh(t) dt.
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 17
In I
2
we substitute cos(t) = u to get
I
2
(x) =
1/2
_
0
e
ixu
(u) du
with (u) =
cosh( cos
1
(u))

1u
2
. Integrating by parts give
I
2
(x) =
e
ixu
ix
(u)

1/2
0

1
ix
1/2
_
0
e
ixu

(u) du = O(x
1
),
since u stays away from any singularites of and

at 1.
In I
1
, we set u =

2xsin(t/2) to get
I
1
(x) =

2e
ix

x/2
_
0
e
iu
2
cosh
_
2 sin
1
_
u

2x
__
du
_
1
u
2
2x
and so
I
1
(x)

2xe
ix

_
0
e
it
2
dt.
Using
_

0
e
it
2
dt =

2
e
i/4
we have
J

(x) + iY

(x)
_
2
x
e
i(xpi/4/2)
,
which gives the result.
I

:
Again we have
_

0
exp(xcosh t t) dt 0 so we only have to consider the other
integral. We split this in two integrals, on from 0 to /2 and the other from /2 to
. Since cos(t) 0 in the second interval, the second integral is bounded. For the
rst one we set u = 2

xsin(t/2) to get
I

(x) =
e
x

2x
_
0
e

u
2
2
cos
_
2 sin
1
_
u
2

x
__
du
_
1
u
2
4x
+O(1).
If now x , the integral goes to
_

0
e

u
2
2
=
_

2
.
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 18
K

:
Let u = 2

xsinh(t/2). Then
K

(x) =
e
x

_
0
e

u
2
2
cosh
_
2 sinh
1
_
u
2

x
__
du
_
1 +
u
2
4x
.
Again, for x the integral goes to
_

0
e

u
2
2
=
_

2
.
q.e.d.
2.6 Graphs of Bessel functions
Figure 2.2: The Bessel functions J
n
(x) and Y
k
(x).
Figure 2.3: The Bessel functions I
n
(x) and K
n
(x).
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 19
2.7 Integral Transforms
In the last section, we want to compute three of the most used integral transforms. Here
we will restrict to the Bessel function J
0
(x).
Theorem 2.14 (Laplace Transform) We have
L[J
0
](s) =
1

1 + s
2
.
Proof: The Laplace transform of the equation x(y

+y) +y

= 0, which is equivalent to
the Bessel equation of order 0, gives
0 =
d
ds
L[y

+ y] +L[y

]
=
d
ds
(s
2
L[y](s) +L[y](s) sy(0) y

(0)) + sL[y](s) y(0)


= (1 + s
2
)L[y]

(s) sL[y](s),
so L[J
0
](s) =
c

1+s
2
with a constant c. We can compute c through
0 = lim
x
L[J

0
](x) = lim
x
(xL[J
0
](x) J
0
(0)) = c 1.
This means we have
L[J
0
](s) =
1

1 + s
2
.
q.e.d.
Theorem 2.15 (Fourier Transform) For s R we have
F[J
0
](s) =
_
_
_
2

1s
2
, |s| < 1
0, |s| 1
.
Proof: Since J
0

_
2
x
cos(x /4), the Fourier integral will diverge unless s is real.
For real s we can write
F[J
0
](s) = lim
0

J
0
(t)e
ist|t|
dt
= lim
0
_
_

_
0
J
0
(t)e
t(is)
dt +

_
0
J
0
(t)e
t(+is)
dt
_
_
Martin Kreh The Bessel Functions
2 Properties of the Bessel functions 20
= lim
0
_
1
_
1 + ( is)
2
+
1
_
1 + ( + is)
2
_
=
_
_
_
2

1s
2
, |s| < 1
0, |s| 1
,
where we have used the Laplace transform. q.e.d.
Theorem 2.16 (Mellin transform) For 0 < (s) < 1 we have
M[J
0
](s) =
2
s1

sin
_
s
2
_

_
s
2
_
2
.
Proof: We use the integral representation for J
0
. Since 0 < (s) < 1, we can interchange
the two occuring integrals. The substitution y = xsin(t) then yields
M[J
0
](s) =
1

_
0

_
0
x
s1
cos(xsin(t)) dxdt
=
1

_
0
sin(t)
s
dt

_
0
y
s1
cos(y) dy.
Using

_
0
t
s1
cos(t) dt = cos
_
s
2
_
(s) and

_
0
sin(t)
s
dt =

tan
_
s
2
_
(
s
2
)
(
s+1
2
)
and the duplication formula of the Gamma function gives
M[J
0
](s) =
1

tan
_
s
2
_
cos
_
s
2
_

_
s
2
_
(s)
(
s+1
2
)
=
2
s1

sin
_
s
2
_

_
s
2
_
2
.
q.e.d.
Martin Kreh The Bessel Functions
References 21
References
[Coh07] Cohen, Henri: Number Theory Volume II: Analytic and Modern Tools. Springer,
2007
[Dav01] Davies, Brian: Integral Transforms and Their Applications. Third Edition.
Springer, 2001
[GR00] Gradshteyn, I.S. ; Ryzhik, I.M.: Table of Integrals, Series and Products.
Sixth Edition. Academic Press, 2000
[Wat22] Watson, G.N.: A Treatise on the Theory of Bessel Functions. Cambridge
University Press, 1922
Martin Kreh The Bessel Functions